Environment-friendly wastewater treatment agent and preparation method thereof

By using corn core activated carbon, natural zigzag pores, NIFE2O4 magnetic materials and polyethylene glycol surface active agents, as well as GQDS prepared by corn straw, a high -efficiency, environmental protection, low -cost wastewater treatment agent is formed, which solves the present. There is the limitations of wastewater treatment materials in technology, and the effect of wastewater treatment effects in multi -field applications has been achieved.

CN119346083AActive Publication Date: 2025-01-24SHANDONG POLYTECHNIC COLLEGE
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411901693.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-01-24
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

Existing wastewater treatment materials have problems such as harmful substances, single application fields, low efficiency and high cost, and it is difficult to meet the complex needs of different types of wastewater treatment.

Method used

Corn cobs are used to prepare activated carbon, and natural zeolite is used to create pores, combined with NiFe2O4 magnetic material and polyethylene glycol surfactant to form an adsorption film. At the same time, corn straw was used to prepare GQDs to broaden the light absorption range and photocatalytic performance.

Benefits of technology

Achieve efficient, environmentally friendly, and low -cost wastewater treatment, can effectively remove heavy metals and other pollutants, suitable for multi -field applications, and solve the problem of complex wastewater pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346083A_ABST
    Figure CN119346083A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of wastewater treatment agent synthesis, and particularly relates to an environment-friendly wastewater treatment agent and a preparation method thereof.The environment-friendly wastewater treatment agent is prepared from 6-9 parts of corncob, 3-5 parts of natural zeolite, 8-10 parts of polyethylene glycol, 1-3 parts of NiFe2O4, 0.2-0.5 part of GQDs, 1.5-2.5 parts of a phosphoric acid solution and 25 parts of N, N-dimethylformamide; according to the invention, corncob is used as a main material to prepare activated carbon, natural zeolite is used for pore forming and heavy metal adsorption, NiFe2O4 is selected as a magnetic material, polyethylene glycol is used as a surfactant to treat the activated carbon to form an adsorption film to promote adsorption of NiFe2O4, existence of natural zeolite prevents NiFe2O4 from occupying pores of the activated carbon, and corn straw is used for preparing GQDs to broaden the light absorption range and improve the photocatalytic performance. The wastewater treatment agent can be applied to multiple fields, multiple material characteristics are integrated, and the efficiency and the application range of the wastewater treatment agent are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wastewater treatment agent synthesis, and specifically relates to an environmentally friendly wastewater treatment agent and a preparation method thereof. Background Art

[0002] With the rapid development of industry, the amount of wastewater discharged has increased dramatically and its composition has become increasingly complex.

[0003] Currently, there are many types of materials for wastewater treatment, but they often have many limitations. For example, they may contain harmful substances, which will cause secondary pollution to the surrounding environment such as soil and water during or after use, violating the original intention of environmental protection. Moreover, the application fields of these materials are relatively single, and the wastewater treatment process efficiency is low, making it difficult to meet the complex needs of different types of wastewater treatment. Many new and efficient wastewater treatment materials have high R&D and production costs, making them difficult to mass-produce.

[0004] In this context, it is urgent to develop an environmentally friendly wastewater treatment agent that is efficient, environmentally friendly, low-cost and widely applicable. Summary of the invention

[0005] In view of the defects of the prior art, the present invention first starts from the concept of green environmental protection, selects corn cobs as the main material to prepare activated carbon, and in order to obtain porous activated carbon materials, selects natural zeolites as pore-forming agents to form pores in the activated carbon. At the same time, natural zeolites themselves can also be used as an adsorption material to replace heavy metal materials in wastewater. In order to broaden the application scope of the treatment agent, NiFe2O4 is selected as a magnetic material. In order to improve the adsorption of NiFe2O4 on the surface of the activated carbon material and maximize the efficiency of wastewater treatment, polyethylene glycol is selected as a surfactant to treat the activated carbon material to form an adsorption film to enhance the adsorption of NiFe2O4. The presence of natural zeolites also avoids the NiFe2O4 material from occupying too many pores of the activated carbon while being adsorbed on the surface of the activated carbon. Corn stalks are further selected as raw materials to prepare GQDs (graphene quantum dots), which broadens the light absorption range of the wastewater treatment agent, improves the optical properties of photocatalysis, and realizes the multi-field application of the wastewater treatment agent.

[0006] To achieve the above object, the technical solution adopted by the present invention is an environmentally friendly wastewater treatment agent, which is prepared from the following raw materials: 6-9 parts of corn cobs, 3-5 parts of natural zeolite, 8-10 parts of polyethylene glycol, 1-3 parts of NiFe2O4, 0.2-0.5 parts of GQDs, 1.5-2.5 parts of phosphoric acid solution and 25 parts of N,N-dimethylformamide;

[0007] Furthermore, the preparation method of NiFe2O4 comprises the following steps:

[0008] (i) Weighing nickel nitrate and dissolving it in ethylene glycol with stirring, wherein the ratio of nickel nitrate to ethylene glycol is 0.9-1.5 g:50 ml, the stirring speed is 500 r / min, and the stirring time is 30 min, to obtain nickel liquid; Weighing ferric nitrate and dissolving it in ethylene glycol with stirring, wherein the ratio of ferric nitrate to ethylene glycol is 3-4.5 g:50 ml, the stirring speed is 500 r / min, and the stirring time is 30 min, to obtain iron liquid; slowly pouring the nickel liquid into the iron liquid, heating and stirring, the heating temperature is 90-120° C., the stirring time is 2 h, the stirring speed is 500 r / min, and cooling to room temperature to obtain a nickel-iron mixed liquid;

[0009] (ii) slowly adding nitric acid solution to the nickel-iron mixed solution obtained in step (i), adjusting the pH range to 2-5, the concentration of the nitric acid solution to 4 mol / L, heating and stirring, the heating temperature is 60-80°C, the heating time is 1h, the stirring speed is 500r / min, and drying is carried out in a vacuum drying oven, the drying temperature is 90°C, and the drying time is 24h to obtain a nickel-iron activated body, heating the nickel-iron activated body, the heating temperature is 400-500°C, the heating time is 2h, and the heating rate is 10°C / min to obtain a NiFe2O4 precursor, the NiFe2O4 precursor is reheated, the reheating temperature is 700-900°C, the reheating rate is 5°C / min, and the heating time is 2h, and naturally cooled to room temperature to obtain NiFe2O4.

[0010] Furthermore, the preparation method of GQDs comprises the following steps:

[0011] (a) Weighing corn stalks, anhydrous ethanol, nitric acid solution and triethylamine in the proportions of 6-10 g: 50 ml: 2.5-5 ml and 10-15 ml respectively, washing, drying and crushing the corn stalks, and sieving them with a mesh of 40 mesh to obtain stalk fine particles;

[0012] (b) adding the straw fine particles obtained in step (a) into anhydrous ethanol for stirring and pretreatment, filtering and drying to obtain a softened straw fine particle body;

[0013] (c) adding triethylamine to deionized water and stirring evenly to obtain a mixed solution, adding the softened straw fine particles obtained in step (b) to the mixed solution and stirring, slowly adding nitric acid solution dropwise to obtain a reaction mixed solution, adding the reaction mixed solution to a hydrothermal kettle for hydrothermal treatment at a hydrothermal temperature of 180-220° C. for a hydrothermal time of 15 h, and cooling to room temperature to obtain a GQDs precursor solution;

[0014] (d) The GQDs precursor liquid obtained in step (c) was centrifuged at a speed of 15000 r / min for 30 min to obtain a supernatant, and the supernatant was dialyzed using a dialysis bag with a molecular weight cutoff of 300D-500D for 24 h to obtain a dialysate, and the dialysate was dried at a drying temperature of 65°C for 24 h to obtain GQDs.

[0015] The present invention also provides a method for preparing an environmentally friendly wastewater treatment agent, comprising the following steps:

[0016] Step 1, weigh 6-9 parts of corn cobs, 3-5 parts of natural zeolite, 8-10 parts of polyethylene glycol, 1-3 parts of NiFe2O4, 0.2-0.5 parts of GQDs, 1.5-2.5 parts of phosphoric acid solution and 25 parts of N,N-dimethylformamide, wash, dry and crush the corn cobs, sieve with a mesh of 20 mesh to obtain corn cob fine particles, pretreat the natural zeolite, sieve with a mesh of 80 mesh to obtain zeolite fine powder;

[0017] Step 2: Add the corncob fine particles obtained in step 1 into N,N-dimethylformamide and soak for 6 hours, add the zeolite fine powder obtained in step 1, stir and ultrasonically treat, the ultrasonic power is 20-40kHz, the ultrasonic time is 30 minutes, filter and dry to obtain a powder material;

[0018] Step 3: Grind the powder material obtained in step 2 and carbonize it under argon atmosphere at a carbonization temperature of 300-500°C for 2 hours at a heating rate of 10°C / min, and cool it to room temperature to obtain carbonized powder;

[0019] Step 4: Add the carbonized powder obtained in step 3 into deionized water and stir evenly, the ratio of activated carbon to deionized water is 1g:10ml, slowly add phosphoric acid solution, then activate it, cool it to room temperature, add sodium carbonate solution to adjust the pH to neutral, stir and filter, wash and dry it to obtain optimized carbonized powder;

[0020] Step 5. Add the polyethylene glycol weighed in step 1 to deionized water and stir evenly. The ratio of polyethylene glycol to water is 1:15 to obtain an activated aqueous solution. Add the optimized carbonized powder obtained in step 4 to the activated aqueous solution and stir. Add GQDs and continue stirring. Then add NiFe2O4 to ultrasound to obtain a mixed reaction liquid. The mixed reaction liquid is further hydrothermally treated at a temperature of 110-150°C for 12 hours. Cool to room temperature to obtain a precipitate. Wash and dry the precipitate to obtain an environmentally friendly wastewater treatment agent.

[0021] The beneficial effects achieved by the present invention are as follows:

[0022] The environmentally friendly wastewater treatment agent prepared by the present invention focuses on corn cobs, which are abundant and renewable resources, during the research and development process of the wastewater treatment agent, and determines them as the main material for preparing activated carbon for the first time. In order to give the activated carbon an ideal porous structure, natural zeolite is selected as a pore-forming agent. In the preparation process, natural zeolite plays a key role. Its unique structure interacts with the activated carbon, successfully constructs abundant pores inside the activated carbon, and greatly increases the specific surface area. At the same time, the natural zeolite itself has excellent adsorption performance. When treating wastewater, it can effectively undergo a replacement reaction with the heavy metal ions therein, thereby separating the heavy metals from the wastewater, which not only realizes the optimization of the activated carbon structure, but also directly participates in the removal of wastewater pollutants, laying a solid foundation for the entire wastewater treatment system.

[0023] The environmentally friendly wastewater treatment agent prepared by the present invention introduces NiFe2O4 as a magnetic material for the first time in order to further expand the breadth and depth of application of the treatment agent. Considering that NiFe2O4 can be efficiently adsorbed on the surface of the activated carbon material, thereby maximizing the wastewater treatment efficiency, polyethylene glycol is selected as a surfactant. Polyethylene glycol can form a uniform and stable adsorption film on the surface of the activated carbon, providing a good attachment site for NiFe2O4 and significantly enhancing its adsorption effect. It is worth mentioning that due to the presence of natural zeolite, in the process of NiFe2O4 being adsorbed on the surface of the activated carbon, it can effectively avoid excessive occupation of the pores of the activated carbon, thereby ensuring the integrity of the activated carbon structure and the stability of the adsorption performance; on this basis, corn stalks are also used as raw materials to prepare GQDs. The addition of GQDs broadens the light absorption range of the wastewater treatment agent, greatly improves the optical properties of photocatalysis, and enables the treatment agent to play an important role in the field of photocatalysis, thereby realizing a wide range of applications in wastewater treatment in multiple fields, and providing a comprehensive and innovative solution for solving complex wastewater pollution problems.

[0024] The environmentally friendly wastewater treatment agent prepared by the present invention takes environmental protection, high efficiency and low cost as key considerations for the first time, and can better meet the needs of wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A diagram showing a preparation method according to an embodiment of the present invention;

[0026] Figure 2 Phase spectrum of NiFe2O4 prepared in the embodiment of the present invention;

[0027] Figure 3 This is a SEM image of the environmentally friendly wastewater treatment agent prepared by the present invention;

[0028] Figure 4This is the TEM image of the environmentally friendly wastewater treatment agent;

[0029] Figure 5 This is a high-resolution TEM image of an environmentally friendly wastewater treatment agent;

[0030] Figure 6 The photoreaction removal diagram of tetracycline in wastewater under photocatalytic conditions for environmentally friendly wastewater treatment agents;

[0031] Figure 7 It is an environmentally friendly wastewater treatment agent used for the removal of heavy metal ions by adsorption;

[0032] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0034] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0035] The preparation methods in the following examples are referred to Figure 1 , unless otherwise specified, are conventional methods; the materials used in the following embodiments, unless otherwise specified, the saturated solutions in the present invention are all the solubility corresponding to the materials under 25°C conditions, and the prepared solutions select mordenite as the natural zeolite.

[0036] Example 1: An environmentally friendly wastewater treatment agent is prepared from the following raw materials in parts by weight: 6 parts of corn cobs, 3 parts of mordenite, 8 parts of polyethylene glycol, 1 part of NiFe2O4, 0.2 parts of GQDs, 1.5 parts of phosphoric acid solution and 25 parts of N,N-dimethylformamide;

[0037] The preparation method of NiFe2O4 comprises the following steps:

[0038] (i) 0.9 g of nickel nitrate hexahydrate was dissolved in 50 ml of ethylene glycol and stirred at a speed of 500 r / min for 30 min to obtain a nickel solution; 3 g of ferric nitrate nonahydrate was dissolved in 50 ml of ethylene glycol and stirred at a speed of 500 r / min for 30 min to obtain an iron solution; the nickel solution was slowly poured into the iron solution, the temperature was heated to 90° C. and stirred at a speed of 500 r / min for 2 h, and naturally cooled to room temperature to obtain a nickel-iron mixed solution;

[0039] (ii) slowly adding nitric acid solution to the nickel-iron mixed solution obtained in step (i), adjusting the pH value to 2 and the concentration of the nitric acid solution to 4 mol / L, heating the mixture to 60°C and stirring at a speed of 500 r / min for 1 h, drying the mixture in a vacuum drying oven at 90°C for 24 h to obtain a nickel-iron activated body, placing the nickel-iron activated body in a muffle furnace and heating it from room temperature to 400°C for 2 h at a heating rate of 10°C / min to obtain a NiFe2O4 precursor, and reheating the NiFe2O4 precursor to 700°C for 2 h at a reheating rate of 5°C / min to obtain NiFe2O4.

[0040] The preparation method of GQDs comprises the following steps:

[0041] (a) Weigh 6 g corn stalks, wash, dry and crush them, and sieve them using a 40-mesh screen to obtain stalk fine particles;

[0042] (b) adding the straw fine particles obtained in step (a) into 50 ml of anhydrous ethanol and stirring for pretreatment for 30 minutes, filtering and placing in a forced air drying oven at 55° C. for drying for 24 hours to obtain a softened straw fine particle body;

[0043] (c) 10 ml of triethylamine was added to 50 ml of deionized water and stirred evenly to obtain a mixed solution, the softened straw fine particles obtained in step (b) were added to the mixed solution and stirred, 2.5 ml of nitric acid solution with a concentration of 3 mol / L was slowly added dropwise to obtain a reaction mixture, the reaction mixture was added to a hydrothermal autoclave for hydrothermal treatment at 180° C. for 15 h, and naturally cooled to room temperature to obtain a GQDs precursor solution;

[0044] (d) The GQDs precursor liquid obtained in step (c) was centrifuged at a rotation speed of 15000 r / min for 30 min to obtain a supernatant, and the supernatant was dialyzed using a dialysis bag with a molecular weight cutoff of 300D for 24 h to obtain a dialysate, and the dialysate was dried in a forced air drying oven at 65°C for 24 h to obtain GQDs.

[0045] This embodiment also provides a method for preparing an environmentally friendly wastewater treatment agent, comprising the following steps:

[0046] Step 1, weigh 6 parts of corn cobs and 3 parts of mordenite, wash, dry and crush the corn cobs, sieve them with a 20-mesh screen to obtain corn cob fine particles, pre-treat the mordenite, and sieve them with an 80-mesh screen to obtain zeolite fine powder;

[0047] Step 2: Add the corncob fine particles obtained in step 1 into 25 parts of N,N-dimethylformamide and soak for 6 hours, add the zeolite fine powder obtained in step 1, stir for 30 minutes at a speed of 500 r / min, and ultrasonically treat for 30 minutes at a power of 20 kHz, filter and dry in a blast drying oven at 55° C. for 24 hours to obtain a powder material;

[0048] Step 3: Grind the powder material obtained in step 2 and carbonize it in a tube furnace at 300°C for 2h in an argon atmosphere of 100ml / min at a heating rate of 10°C / min, and naturally cool it to room temperature to obtain a carbonized powder;

[0049] Step 4: Add the carbonized powder obtained in step 3 to deionized water and stir evenly, the ratio of activated carbon to deionized water is 1g:10ml, slowly drop 1.5 parts of 2mol / L phosphoric acid solution, then activate it, naturally cool it to room temperature, add saturated sodium carbonate solution to adjust the pH to neutral, stir and filter, wash it with deionized water 3 times and dry it in a blast drying oven at 55°C for 24h to obtain optimized carbonized powder;

[0050] Step 5. Weigh 8 parts of polyethylene glycol-400 and add them to 48 ml of deionized water and stir evenly to obtain an activated aqueous solution. Add the optimized carbonized powder obtained in step 4 to the activated aqueous solution and stir for 30 minutes. Add 0.2 parts of GQDs and continue stirring for 30 minutes. Then add 1 part of NiFe2O4 and ultrasonically treat it at a power of 20 kHz for 30 minutes. Further heat it to 110°C and hydrothermally treat it in a hydrothermal kettle for 12 hours. Naturally cool it to room temperature to obtain a precipitate. Wash the precipitate with deionized water 3 times and dry it in a forced air drying oven at 55°C for 24 hours to obtain an environmentally friendly wastewater treatment agent.

[0051] Example 2: An environmentally friendly wastewater treatment agent is prepared from the following raw materials in parts by weight: 7.5 parts of corn cobs, 4 parts of mordenite, 9 parts of polyethylene glycol, 2 parts of NiFe2O4, 0.35 parts of GQDs, 2 parts of phosphoric acid solution and 25 parts of N,N-dimethylformamide;

[0052] The preparation method of NiFe2O4 comprises the following steps:

[0053] (i) 1.2 g of nickel nitrate hexahydrate was dissolved in 50 ml of ethylene glycol and stirred at a speed of 500 r / min for 30 min to obtain a nickel solution; 3.8 g of ferric nitrate nonahydrate was dissolved in 50 ml of ethylene glycol and stirred at a speed of 500 r / min for 30 min to obtain an iron solution; the nickel solution was slowly poured into the iron solution, the temperature was heated to 110° C. and stirred at a speed of 500 r / min for 2 h, and naturally cooled to room temperature to obtain a nickel-iron mixed solution;

[0054] (ii) slowly adding nitric acid solution to the nickel-iron mixed solution obtained in step (i), adjusting the pH value to 3.5 and the concentration of the nitric acid solution to 4 mol / L, heating the mixture to 70°C and stirring at a speed of 500 r / min for 1 h, drying the mixture in a vacuum drying oven at 90°C for 24 h to obtain a nickel-iron activated body, placing the nickel-iron activated body in a muffle furnace and heating it from room temperature to 450°C for 2 h at a heating rate of 10°C / min to obtain a NiFe2O4 precursor, and reheating the NiFe2O4 precursor to 800°C for 2 h at a reheating rate of 5°C / min to obtain NiFe2O4.

[0055] The preparation method of GQDs comprises the following steps:

[0056] (a) Weigh 8 g of corn stalks, wash, dry and crush them, and sieve them using a 40-mesh screen to obtain stalk fine particles;

[0057] (b) adding the straw fine particles obtained in step (a) into 50 ml of anhydrous ethanol and stirring for pretreatment for 30 minutes, filtering and placing in a forced air drying oven at 55° C. for drying for 24 hours to obtain a softened straw fine particle body;

[0058] (c) 13 ml of triethylamine was added to 50 ml of deionized water and stirred evenly to obtain a mixed solution, the softened straw fine particles obtained in step (b) were added to the mixed solution and stirred, 4 ml of 3 mol / L nitric acid solution was slowly added dropwise to obtain a reaction mixture, the reaction mixture was added to a hydrothermal autoclave for hydrothermal treatment at 200 °C for 15 h, and naturally cooled to room temperature to obtain a GQDs precursor solution;

[0059] (d) The GQDs precursor liquid obtained in step (c) was centrifuged at a rotation speed of 15000 r / min for 30 min to obtain a supernatant, and the supernatant was dialyzed using a dialysis bag with a molecular weight cutoff of 400D for 24 h to obtain a dialysate, and the dialysate was dried in a forced air drying oven at 65°C for 24 h to obtain GQDs.

[0060] This embodiment also provides a method for preparing an environmentally friendly wastewater treatment agent, comprising the following steps:

[0061] Step 1, weighing 7.5 parts of corn cobs and 4 parts of mordenite, washing, drying and crushing the corn cobs, sieving with a 20-mesh screen to obtain corn cob fine particles, pre-treating the mordenite, and sieving with an 80-mesh screen to obtain zeolite fine powder;

[0062] Step 2: Add the corncob fine particles obtained in step 1 into 25 parts of N,N-dimethylformamide and soak for 6 hours, add the zeolite fine powder obtained in step 1, stir for 30 minutes at a speed of 500 r / min, and ultrasonically treat for 30 minutes at a power of 30 kHz, filter and dry in a blast drying oven at 55° C. for 24 hours to obtain a powder material;

[0063] Step 3: Grind the powder material obtained in step 2 and carbonize it in a tube furnace at 400°C for 2h in an argon atmosphere of 100ml / min at a heating rate of 10°C / min, and naturally cool it to room temperature to obtain a carbonized powder;

[0064] Step 4: Add the carbonized powder obtained in step 3 to deionized water and stir evenly. The ratio of activated carbon to deionized water is 1 g: 10 ml. Slowly drop 2 portions of 2 mol / L phosphoric acid solution, and then activate it. Naturally cool it to room temperature. Add saturated sodium carbonate solution to adjust the pH to neutral, stir and filter it. Wash it 3 times with deionized water and dry it in a blast drying oven at 55 ° C for 24 hours to obtain optimized carbonized powder.

[0065] Step 5. Weigh 9 parts of polyethylene glycol-400 and add them to 54 ml of deionized water and stir evenly to obtain an activated aqueous solution. Add the optimized carbonized powder obtained in step 4 to the activated aqueous solution and stir for 30 minutes. Add 0.35 parts of GQDs and continue stirring for 30 minutes. Then add 2 parts of NiFe2O4 and ultrasonically treat it at a power of 20 kHz for 30 minutes. Further heat it to 130°C and hydrothermally treat it in a hydrothermal kettle for 12 hours. Naturally cool it to room temperature to obtain a precipitate. Wash the precipitate with deionized water 3 times and dry it in a forced air drying oven at 55°C for 24 hours to obtain an environmentally friendly wastewater treatment agent.

[0066] Embodiment 3:

[0067] An environmentally friendly wastewater treatment agent is prepared from the following raw materials: 9 parts of corn cobs, 5 parts of mordenite, 10 parts of polyethylene glycol, 3 parts of NiFe2O4, 0.5 parts of GQDs, 2.5 parts of phosphoric acid solution and 25 parts of N,N-dimethylformamide;

[0068] The preparation method of NiFe2O4 comprises the following steps:

[0069] (i) 1.5 g of nickel nitrate hexahydrate was dissolved in 50 ml of ethylene glycol and stirred at a speed of 500 r / min for 30 min to obtain a nickel solution; 4.5 g of ferric nitrate nonahydrate was dissolved in 50 ml of ethylene glycol and stirred at a speed of 500 r / min for 30 min to obtain an iron solution; the nickel solution was slowly poured into the iron solution, the temperature was heated to 120° C. and stirred at a speed of 500 r / min for 2 h, and naturally cooled to room temperature to obtain a nickel-iron mixed solution;

[0070] (ii) slowly adding nitric acid solution to the nickel-iron mixed solution obtained in step (i), adjusting the pH value to 5 and the concentration of the nitric acid solution to 4 mol / L, heating the mixture to 80°C and stirring at a speed of 500 r / min for 1 h, drying the mixture in a vacuum drying oven at 90°C for 24 h to obtain a nickel-iron activated body, placing the nickel-iron activated body in a muffle furnace and heating it from room temperature to 500°C and maintaining it for 2 h at a heating rate of 10°C / min to obtain a NiFe2O4 precursor, and reheating the NiFe2O4 precursor to 900°C and maintaining it for 2 h at a secondary heating rate of 5°C / min to obtain NiFe2O4.

[0071] The preparation method of GQDs comprises the following steps:

[0072] (a) Weigh 10 g corn stalks, wash, dry and crush them, and sieve them using a 40-mesh screen to obtain stalk fine particles;

[0073] (b) adding the straw fine particles obtained in step (a) into 50 ml of anhydrous ethanol and stirring for pretreatment for 30 minutes, filtering and placing in a forced air drying oven at 55° C. for drying for 24 hours to obtain a softened straw fine particle body;

[0074] (c) 15 ml of triethylamine was added to 50 ml of deionized water and stirred evenly to obtain a mixed solution, the softened straw fine particles obtained in step (b) were added to the mixed solution and stirred, 5 ml of 3 mol / L nitric acid solution was slowly added dropwise to obtain a reaction mixture, the reaction mixture was added to a hydrothermal autoclave for hydrothermal treatment at 220 ° C for 15 h, and naturally cooled to room temperature to obtain a GQDs precursor solution;

[0075] (d) The GQDs precursor liquid obtained in step (c) was centrifuged at a rotation speed of 15000 r / min for 30 min to obtain a supernatant, and the supernatant was dialyzed using a dialysis bag with a molecular weight cutoff of 500D for 24 h to obtain a dialysate, and the dialysate was dried in a forced air drying oven at 65°C for 24 h to obtain GQDs.

[0076] This embodiment also provides a method for preparing an environmentally friendly wastewater treatment agent, comprising the following steps:

[0077] Step 1, weigh 9 parts of corn cobs and 5 parts of mordenite, wash, dry and crush the corn cobs, sieve them with a 20-mesh screen to obtain corn cob fine particles, pretreat the mordenite, and sieve them with an 80-mesh screen to obtain zeolite fine powder;

[0078] Step 2: Add the corncob fine particles obtained in step 1 into 25 parts of N,N-dimethylformamide and soak for 6 hours, add the zeolite fine powder obtained in step 1, stir for 30 minutes at a speed of 500 r / min, and ultrasonically treat for 30 minutes at a power of 40 kHz, filter and dry in a blast drying oven at 55° C. for 24 hours to obtain a powder material;

[0079] Step 3: Grind the powder material obtained in step 2 and carbonize it in a tube furnace at 500° C. for 2 h in an argon atmosphere of 100 ml / min at a heating rate of 10° C. / min, and naturally cool it to room temperature to obtain a carbonized powder;

[0080] Step 4: Add the carbonized powder obtained in step 3 to deionized water and stir evenly. The ratio of activated carbon to deionized water is 1 g: 10 ml. Slowly drop 2.5 parts of 2 mol / L phosphoric acid solution, then activate it, cool it naturally to room temperature, add saturated sodium carbonate solution to adjust the pH to neutral, stir and filter, wash it with deionized water 3 times, and dry it in a forced air drying oven at 55 ° C for 24 hours to obtain optimized carbonized powder.

[0081] Step 5. Weigh 10 parts of polyethylene glycol-400 and add them to 60 ml of deionized water and stir evenly to obtain an activated aqueous solution. Add the optimized carbonized powder obtained in step 4 to the activated aqueous solution and stir for 30 minutes. Add 0.5 parts of GQDs and continue stirring for 30 minutes. Then add 3 parts of NiFe2O4 and ultrasonically treat it at a power of 20 kHz for 30 minutes. Further heat it to 150°C and hydrothermally treat it in a hydrothermal kettle for 12 hours. Naturally cool it to room temperature to obtain a precipitate. Wash the precipitate with deionized water 3 times and dry it in a forced air drying oven at 55°C for 24 hours to obtain an environmentally friendly wastewater treatment agent.

[0082] Comparative Example:

[0083] The difference between Comparative Example 1 and Example 2 is that no mordenite is added, and the rest is the same as Example 2;

[0084] The difference between Comparative Example 2 and Example 2 is that NiFe2O4 is not added, and the rest is the same as Example 2;

[0085] The difference between Comparative Example 3 and Example 2 is that no GQDs are added, and the rest is the same as Example 2;

[0086] The difference between Comparative Example 4 and Example 2 is that NiFe2O4 and GQDs are not added, and the rest is the same as Example 2;

[0087] The difference between Comparative Example 5 and Example 2 is that no mordenite and NiFe2O4 are added, and the rest is the same as Example 2;

[0088] The difference between Comparative Example 6 and Example 2 is that no mordenite, NiFe2O4 and GQDs are added, and the rest is the same as Example 2.

[0089] Figure 2 This is the phase spectrum of NiFe2O4. Figure 2 The diffraction peaks of NiFe2O4 at diffraction angles of 18.39°, 30.29°, 35.69°, 43.36°, 57.35° and 62.91° correspond to NiFe2O4-JCPDS # The 111, 220, 311, 400, 511 and 440 crystal planes of 10-0325 indicate that NiFe2O4 was successfully prepared. At the same time, no other impurity peaks appeared in the figure, indicating that the NiFe2O4 prepared by this method has a high purity; Figure 3 The SEM image of the prepared environmentally friendly wastewater treatment agent shows no large pieces of material, indicating that the material is dispersed relatively evenly; Figure 4 This is the TEM image of the environmentally friendly wastewater treatment agent. It can be seen that the environmentally friendly wastewater treatment agent has a higher porosity. Figure 5 This is a high-resolution TEM image of an environmentally friendly wastewater treatment agent. From the distribution area of ​​the lattice fringes, the corresponding size of the lattice fringes is measured to be D=0.293nm, which corresponds to the size of the (220) crystal plane of NiFe2O4, further indicating that NiFe2O4 was successfully prepared. Figure 5 It can be seen that NiFe2O4, activated carbon and GQDs are closely connected, which further illustrates that the environmentally friendly wastewater treatment agent was successfully prepared.

[0090] In order to verify the treatment effect of the prepared environmentally friendly wastewater treatment agent on wastewater, a 50 mg / L tetracycline solution was prepared by simulating the wastewater environment. 30 mg of the environmentally friendly wastewater treatment agent was weighed and put into 100 ml of the tetracycline solution. The optical degradation of the environmentally friendly wastewater treatment agent on tetracycline was measured under visible light conditions using a 300W xenon lamp. Figure 6 It can be seen that for the embodiment, after 30 minutes of degradation, the content of tetracycline solution is almost zero. For the comparative example prepared, its catalytic activity is significantly weaker than that of the embodiment. In order to further test the performance of the environmentally friendly wastewater treatment agent in the field of adsorption, lead (Pb 2+ ), cadmium (Cd 2+ ) and mercury (Hg2+ ) mixed solution, weigh 30mg of environmentally friendly wastewater treatment agent and put it into 100ml of the mixed solution prepared above, Figure 7 It can be seen that the environmentally friendly wastewater treatment agent prepared in the example shows good performance in the adsorption process of heavy metal ions. After 40 minutes, the heavy metal ions in the solution are almost zero.

[0091] A 20 mg / L iron oxide nanoparticle wastewater mixture was further prepared, 30 mg of an environmentally friendly wastewater treatment agent was weighed and added to more than 100 ml of the prepared wastewater mixture, and the environmentally friendly wastewater treatment agent was used to adsorb the magnetic material.

[0092] Table 1 shows the adsorption results of environmentally friendly wastewater treatment agents on iron oxide nanoparticles:

[0093]

[0094] It can be seen from Table 1 that after 20 minutes of adsorption, the adsorption rate of Example 2 for iron oxide nanoparticles reached 99.3%, showing a relatively high adsorption activity.

[0095] Based on the above analysis, it can be concluded that the prepared environmentally friendly wastewater treatment agent exhibits high performance in different fields.

[0096] Obviously, the above comparative examples and embodiments are only a part of comparative examples and embodiments of the present invention, and they and the comparative examples and embodiments based on such references are all within the scope of protection of the present invention.

[0097] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0098] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. An environmentally friendly wastewater treatment agent, characterized in that: The method is prepared from the following raw materials in parts by weight: 6-9 parts of corn cobs, 3-5 parts of natural zeolite, 8-10 parts of polyethylene glycol, 1-3 parts of NiFe2O4, 0.2-0.5 parts of GQDs, 1.5-2.5 parts of phosphoric acid solution and 25 parts of N,N-dimethylformamide; The raw materials for preparing NiFe2O4 include nickel nitrate and iron nitrate; The preparation method of NiFe2O4 comprises the following steps: (i) weighing nickel nitrate and dissolving it in ethylene glycol and stirring to obtain a nickel liquid, weighing ferric nitrate and dissolving it in ethylene glycol and stirring to obtain an iron liquid, slowly pouring the nickel liquid into the iron liquid, heating and stirring, and cooling to room temperature to obtain a nickel-iron mixed liquid; (ii) adjusting the pH of the nickel-iron mixed solution obtained in step (i), heating and stirring, and drying to obtain a nickel-iron activated body, heating the nickel-iron activated body to obtain a NiFe2O4 precursor, reheating the NiFe2O4 precursor, and cooling to room temperature to obtain NiFe2O4.

2. An environmentally friendly wastewater treatment agent according to claim 1, characterized in that: The nickel nitrate and ethylene glycol in step (i) are used in a ratio of 0.9-1.5 g:50 ml, the iron nitrate and ethylene glycol in a ratio of 3-4.5 g:50 ml, and the pH range in step (ii) is 2-5.

3. An environmentally friendly wastewater treatment agent according to claim 1, characterized in that: The raw materials for preparing the GQDs include corn stalks and triethylamine; The preparation method of GQDs comprises the following steps: (a) weighing corn stalks, crushing and screening to obtain stalk fine particles; (b) measuring anhydrous ethanol, adding the anhydrous ethanol to pre-treat the straw fine particles obtained in step (a) to obtain a softened straw fine particle body; (c) adding triethylamine to deionized water and stirring evenly to obtain a mixed solution, adding the softened straw fine particles obtained in step (b) to the mixed solution and stirring, slowly adding nitric acid solution dropwise to obtain a reaction mixed solution, subjecting the reaction mixed solution to hydrothermal treatment, and cooling to room temperature to obtain a GQDs precursor solution; (d) Centrifuging the GQDs precursor solution obtained in step (c) to obtain a supernatant, dialyzing the obtained supernatant to obtain a dialysate, and drying the dialysate to obtain GQDs.

4. An environmentally friendly wastewater treatment agent according to claim 3, characterized in that: The raw material corn stalk and triethylamine are used in a ratio of 6-10 g:10-15 ml, the hydrothermal temperature in step (c) is 180-220° C., the hydrothermal time is 15 h, the dialysis bag used in the dialysis treatment in step (d) has a molecular weight cutoff of 300D-500D, and the dialysis time is 24 h.

5. A method for preparing an environmentally friendly wastewater treatment agent according to any one of claims 1 to 4, characterized in that: The steps include: Step 1, weigh 6-9 parts of corn cobs, 3-5 parts of natural zeolite, 8-10 parts of polyethylene glycol, 1-3 parts of NiFe2O4, 0.2-0.5 parts of GQDs, 1.5-2.5 parts of phosphoric acid solution and 25 parts of N,N-dimethylformamide, crush and sieve the corn cobs to obtain corn cob fine particles, pre-treat and sieve the natural zeolite to obtain zeolite fine powder; Step 2: soak the corncob granules obtained in step 1 in N,N-dimethylformamide, add the zeolite powder obtained in step 1 thereto, stir and ultrasonicate, filter and dry to obtain a powder material; Step 3: Grinding and carbonizing the powder material obtained in step 2, and cooling to room temperature to obtain carbonized powder; Step 4: Add the carbonized powder obtained in step 3 into deionized water and stir evenly, slowly add phosphoric acid solution, then activate it, cool it to room temperature, adjust the pH to neutral, stir and filter it, wash and dry it to obtain optimized carbonized powder; Step 5: Add the polyethylene glycol weighed in step 1 to deionized water and stir evenly to obtain an activated aqueous solution; add the optimized carbonized powder obtained in step 4 to the activated aqueous solution and stir; add GQDs and continue stirring; then add NiFe2O4 to ultrasound to obtain a mixed reaction solution; hydrothermally heat the mixed reaction solution, cool it to room temperature, obtain a precipitate, wash and dry the precipitate, and obtain an environmentally friendly wastewater treatment agent.

6. The method for preparing an environmentally friendly wastewater treatment agent according to claim 5, characterized in that: The carbonization temperature in step 3 is 300-500°C, the carbonization time is 2h, the ratio of the carbonized powder to deionized water in step 4 is 1:10, the ratio of the polyethylene glycol to water in step 5 is 1:6, the hydrothermal treatment temperature is 110-150°C, and the hydrothermal treatment time is 12h.

Citation Information

Patent Citations

  • Method of one-step synthesizing fluorescent carbon dots with corncob as carbon source

    CN105038781A

  • Heavy metal adsorption material prepared from corn cob and preparation method thereof

    CN106669616A

  • Preparation method of composite carbon material

    CN106833697A

  • Preparation method of mesoporous activated carbon

    CN109081341A

  • Method for manufacturing corncob-based adsorbent for treating cation-containing dye wastewater

    CN109939641A